MENGUAK NILAI-NILAI PENDIDIKAN KARAKTER DALAM KARYA KHALIL GIBRAN - Nahdhiyah, Nahdhiyah (LP2M IAIN Palangka Raya, 2014)
This article aims to expose character education values of Gibranâs statements in his monumental work, The Prophet. The content analysis is used to analyze messages which consist on 26 poetries. From the ten values of character education are dominated by values of faith and takwa,Â the values are found in Poetries of Children, Crime and Punishment, Pain, and Religion. Therefore, teaching literature not only how to teach the structure ofÂ words and sentences, but the most urgent is to teach wisdom values, in this case values of character education as alternative consideration among nation character decance. The Holy Quran build character by stressing inner aspects, both mind and heart.